Chronic tianeptine induces tolerance in analgesia and hyperlocomotion via mu-opioid receptor activation in mice - Allain, Florence; Ehrlich, Aliza T.; McNicholas, Michael; Gross, Florence; Ma, Weiya; Kieffer, Brigitte L.; Darcq, Emmanuel (Frontiers in Psychiatry, 2023)
Tianeptine is approved in some countries to treat depression and anxiety. In addition to its activity on serotonin and glutamate neurotransmission, tianeptine was shown to be a mu opioid receptor (MOR) agonist, but only few preclinical studies have characterized the opioid-like behavioral effects of tianeptine. Here, we tested tianeptine activity on G protein activation using [S35] GTPS binding assay in brain tissue from MOR+/+ and MOR -/- mice. Then, to determine whether tianeptine behavioral responses are MOR dependent, we characterized analgesic, locomotor and rewarding responses of tianeptine in MOR+/+ and MOR -/- mice using tail immersion, hot plate, locomotor and conditioned place preference tests. Using the [S35] GTPS binding assay, we found that tianeptine signaling is mediated by MOR in the brain with properties similar to those of DAMGO (a classic MOR agonist). Furthermore, we found that the MOR is necessary for tianeptine's analgesic (tail immersion and hot plate), locomotor and rewarding (conditioned place preference) effects. Indeed, these behavioral effects could only be measured in MOR+/+ mice, but not in MOR -/- mice. Additionally, chronic administration of tianeptine induced tolerance to its analgesic and hyperlocomotor effects. These findings suggest that tianeptine’s opioid-like effects require MOR and that chronic use could lead to tolerance.